Effect of whole plant extract of Evolvulus alsinoides on thermal stress resistance and longevity in Caenorhabditis elegans - Doshi, Shital Hemal (Brazilian Journal of Science, 2025)
The popular Ayurvedic plant Evolvulus alsinoides is known to have adaptogenic properties. Adaptogens reduce stress and anxiety and thereby promote the overall well-being of the individual. Since chronic stress is associated with lower than normal lifespan expectance, any herbs known to reduce the stress should have the reverse impact. Therefore, this research aimed to study the anti-ageing activity of Evolvulus alsinoides in the well-established aging model Caenorhabditis elegans. The longevity-enhancing impact was assessed under the optimum growth and survival conditions for the C. elegans. Oxidative stress was induced by the use of Paraquat in N2 wild-type C. elegans, and the thermal stress was induced in transgenic C. elegans TJ 356, which expressed Green fluorescence Protein (GFP) under the control of heat shock protein promoters for the visualization of induction of anti-stress genes. The impact of the stress was analyzed by the lifespan analysis, and data were analyzed by the Kaplein Meyer statistical analysis. The results indicated that E. alsinoides extracts dose-dependently increased the mean lifespan of C. elegans by 18.0% and 26.2% at the concentrations of 0.1 mg/mL-1 and 1 mg/mL-1 under optimum growth and survival conditions, respectively. The survival rates of E. alsinoides extract-fed C. elegans have been greater than those of untreated C. elegans against thermal-induced stress. For Oxidative stress, the E. alsinoides treatment was non-significant. It was found that Evolvulus alsinoides extract promotes longevity in Caenorhabditis elegans by promoting stress tolerance and by tinkering with the insulin/IGF signaling pathway.